Bilingualism Strategy Using Video in Teaching English for Young Learners - Wira Mahadika, Muhammad Prastha; Nuraini, Kristi (Institut Agama Islam Tarbiyatut Tholabah, 2025)
This study explores the use of bilingualism in teaching English to Young learners through video-based learning. By integrating videos as a medium, the learning process becomes more interactive, visually appealing, and contextually rich. The study investigates how bilingual videos—featuring explanations, dialogues, and visual aids in both the students' native language and English—enhance vocabulary acquisition, pronunciation, and listening skills. Results indicate that bilingual video-based learning improves understanding and retention, particularly for young learners in a multilingual environment. This approach offers a practical, engaging strategy for early English education, bridging linguistic barriers while cultivating an interest in language learning.